Skip to main content
Solve for x
Tick mark Image
Graph

Similar Problems from Web Search

Share

3\left(x-2\right)\left(x+1\right)\times 2-3\left(x+1\right)^{2}\times 4=\left(x-2\right)\left(x-1\right)
Variable x cannot be equal to any of the values -1,1,2 since division by zero is not defined. Multiply both sides of the equation by 3\left(x-2\right)\left(x-1\right)\left(x+1\right)^{2}, the least common multiple of x^{2}-1,x^{2}-3x+2,3x^{2}+6x+3.
\left(3x-6\right)\left(x+1\right)\times 2-3\left(x+1\right)^{2}\times 4=\left(x-2\right)\left(x-1\right)
Use the distributive property to multiply 3 by x-2.
\left(3x^{2}-3x-6\right)\times 2-3\left(x+1\right)^{2}\times 4=\left(x-2\right)\left(x-1\right)
Use the distributive property to multiply 3x-6 by x+1 and combine like terms.
6x^{2}-6x-12-3\left(x+1\right)^{2}\times 4=\left(x-2\right)\left(x-1\right)
Use the distributive property to multiply 3x^{2}-3x-6 by 2.
6x^{2}-6x-12-3\left(x^{2}+2x+1\right)\times 4=\left(x-2\right)\left(x-1\right)
Use binomial theorem \left(a+b\right)^{2}=a^{2}+2ab+b^{2} to expand \left(x+1\right)^{2}.
6x^{2}-6x-12-12\left(x^{2}+2x+1\right)=\left(x-2\right)\left(x-1\right)
Multiply 3 and 4 to get 12.
6x^{2}-6x-12-\left(12x^{2}+24x+12\right)=\left(x-2\right)\left(x-1\right)
Use the distributive property to multiply 12 by x^{2}+2x+1.
6x^{2}-6x-12-12x^{2}-24x-12=\left(x-2\right)\left(x-1\right)
To find the opposite of 12x^{2}+24x+12, find the opposite of each term.
-6x^{2}-6x-12-24x-12=\left(x-2\right)\left(x-1\right)
Combine 6x^{2} and -12x^{2} to get -6x^{2}.
-6x^{2}-30x-12-12=\left(x-2\right)\left(x-1\right)
Combine -6x and -24x to get -30x.
-6x^{2}-30x-24=\left(x-2\right)\left(x-1\right)
Subtract 12 from -12 to get -24.
-6x^{2}-30x-24=x^{2}-3x+2
Use the distributive property to multiply x-2 by x-1 and combine like terms.
-6x^{2}-30x-24-x^{2}=-3x+2
Subtract x^{2} from both sides.
-7x^{2}-30x-24=-3x+2
Combine -6x^{2} and -x^{2} to get -7x^{2}.
-7x^{2}-30x-24+3x=2
Add 3x to both sides.
-7x^{2}-27x-24=2
Combine -30x and 3x to get -27x.
-7x^{2}-27x-24-2=0
Subtract 2 from both sides.
-7x^{2}-27x-26=0
Subtract 2 from -24 to get -26.
a+b=-27 ab=-7\left(-26\right)=182
To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as -7x^{2}+ax+bx-26. To find a and b, set up a system to be solved.
-1,-182 -2,-91 -7,-26 -13,-14
Since ab is positive, a and b have the same sign. Since a+b is negative, a and b are both negative. List all such integer pairs that give product 182.
-1-182=-183 -2-91=-93 -7-26=-33 -13-14=-27
Calculate the sum for each pair.
a=-13 b=-14
The solution is the pair that gives sum -27.
\left(-7x^{2}-13x\right)+\left(-14x-26\right)
Rewrite -7x^{2}-27x-26 as \left(-7x^{2}-13x\right)+\left(-14x-26\right).
-x\left(7x+13\right)-2\left(7x+13\right)
Factor out -x in the first and -2 in the second group.
\left(7x+13\right)\left(-x-2\right)
Factor out common term 7x+13 by using distributive property.
x=-\frac{13}{7} x=-2
To find equation solutions, solve 7x+13=0 and -x-2=0.
3\left(x-2\right)\left(x+1\right)\times 2-3\left(x+1\right)^{2}\times 4=\left(x-2\right)\left(x-1\right)
Variable x cannot be equal to any of the values -1,1,2 since division by zero is not defined. Multiply both sides of the equation by 3\left(x-2\right)\left(x-1\right)\left(x+1\right)^{2}, the least common multiple of x^{2}-1,x^{2}-3x+2,3x^{2}+6x+3.
\left(3x-6\right)\left(x+1\right)\times 2-3\left(x+1\right)^{2}\times 4=\left(x-2\right)\left(x-1\right)
Use the distributive property to multiply 3 by x-2.
\left(3x^{2}-3x-6\right)\times 2-3\left(x+1\right)^{2}\times 4=\left(x-2\right)\left(x-1\right)
Use the distributive property to multiply 3x-6 by x+1 and combine like terms.
6x^{2}-6x-12-3\left(x+1\right)^{2}\times 4=\left(x-2\right)\left(x-1\right)
Use the distributive property to multiply 3x^{2}-3x-6 by 2.
6x^{2}-6x-12-3\left(x^{2}+2x+1\right)\times 4=\left(x-2\right)\left(x-1\right)
Use binomial theorem \left(a+b\right)^{2}=a^{2}+2ab+b^{2} to expand \left(x+1\right)^{2}.
6x^{2}-6x-12-12\left(x^{2}+2x+1\right)=\left(x-2\right)\left(x-1\right)
Multiply 3 and 4 to get 12.
6x^{2}-6x-12-\left(12x^{2}+24x+12\right)=\left(x-2\right)\left(x-1\right)
Use the distributive property to multiply 12 by x^{2}+2x+1.
6x^{2}-6x-12-12x^{2}-24x-12=\left(x-2\right)\left(x-1\right)
To find the opposite of 12x^{2}+24x+12, find the opposite of each term.
-6x^{2}-6x-12-24x-12=\left(x-2\right)\left(x-1\right)
Combine 6x^{2} and -12x^{2} to get -6x^{2}.
-6x^{2}-30x-12-12=\left(x-2\right)\left(x-1\right)
Combine -6x and -24x to get -30x.
-6x^{2}-30x-24=\left(x-2\right)\left(x-1\right)
Subtract 12 from -12 to get -24.
-6x^{2}-30x-24=x^{2}-3x+2
Use the distributive property to multiply x-2 by x-1 and combine like terms.
-6x^{2}-30x-24-x^{2}=-3x+2
Subtract x^{2} from both sides.
-7x^{2}-30x-24=-3x+2
Combine -6x^{2} and -x^{2} to get -7x^{2}.
-7x^{2}-30x-24+3x=2
Add 3x to both sides.
-7x^{2}-27x-24=2
Combine -30x and 3x to get -27x.
-7x^{2}-27x-24-2=0
Subtract 2 from both sides.
-7x^{2}-27x-26=0
Subtract 2 from -24 to get -26.
x=\frac{-\left(-27\right)±\sqrt{\left(-27\right)^{2}-4\left(-7\right)\left(-26\right)}}{2\left(-7\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -7 for a, -27 for b, and -26 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-27\right)±\sqrt{729-4\left(-7\right)\left(-26\right)}}{2\left(-7\right)}
Square -27.
x=\frac{-\left(-27\right)±\sqrt{729+28\left(-26\right)}}{2\left(-7\right)}
Multiply -4 times -7.
x=\frac{-\left(-27\right)±\sqrt{729-728}}{2\left(-7\right)}
Multiply 28 times -26.
x=\frac{-\left(-27\right)±\sqrt{1}}{2\left(-7\right)}
Add 729 to -728.
x=\frac{-\left(-27\right)±1}{2\left(-7\right)}
Take the square root of 1.
x=\frac{27±1}{2\left(-7\right)}
The opposite of -27 is 27.
x=\frac{27±1}{-14}
Multiply 2 times -7.
x=\frac{28}{-14}
Now solve the equation x=\frac{27±1}{-14} when ± is plus. Add 27 to 1.
x=-2
Divide 28 by -14.
x=\frac{26}{-14}
Now solve the equation x=\frac{27±1}{-14} when ± is minus. Subtract 1 from 27.
x=-\frac{13}{7}
Reduce the fraction \frac{26}{-14} to lowest terms by extracting and canceling out 2.
x=-2 x=-\frac{13}{7}
The equation is now solved.
3\left(x-2\right)\left(x+1\right)\times 2-3\left(x+1\right)^{2}\times 4=\left(x-2\right)\left(x-1\right)
Variable x cannot be equal to any of the values -1,1,2 since division by zero is not defined. Multiply both sides of the equation by 3\left(x-2\right)\left(x-1\right)\left(x+1\right)^{2}, the least common multiple of x^{2}-1,x^{2}-3x+2,3x^{2}+6x+3.
\left(3x-6\right)\left(x+1\right)\times 2-3\left(x+1\right)^{2}\times 4=\left(x-2\right)\left(x-1\right)
Use the distributive property to multiply 3 by x-2.
\left(3x^{2}-3x-6\right)\times 2-3\left(x+1\right)^{2}\times 4=\left(x-2\right)\left(x-1\right)
Use the distributive property to multiply 3x-6 by x+1 and combine like terms.
6x^{2}-6x-12-3\left(x+1\right)^{2}\times 4=\left(x-2\right)\left(x-1\right)
Use the distributive property to multiply 3x^{2}-3x-6 by 2.
6x^{2}-6x-12-3\left(x^{2}+2x+1\right)\times 4=\left(x-2\right)\left(x-1\right)
Use binomial theorem \left(a+b\right)^{2}=a^{2}+2ab+b^{2} to expand \left(x+1\right)^{2}.
6x^{2}-6x-12-12\left(x^{2}+2x+1\right)=\left(x-2\right)\left(x-1\right)
Multiply 3 and 4 to get 12.
6x^{2}-6x-12-\left(12x^{2}+24x+12\right)=\left(x-2\right)\left(x-1\right)
Use the distributive property to multiply 12 by x^{2}+2x+1.
6x^{2}-6x-12-12x^{2}-24x-12=\left(x-2\right)\left(x-1\right)
To find the opposite of 12x^{2}+24x+12, find the opposite of each term.
-6x^{2}-6x-12-24x-12=\left(x-2\right)\left(x-1\right)
Combine 6x^{2} and -12x^{2} to get -6x^{2}.
-6x^{2}-30x-12-12=\left(x-2\right)\left(x-1\right)
Combine -6x and -24x to get -30x.
-6x^{2}-30x-24=\left(x-2\right)\left(x-1\right)
Subtract 12 from -12 to get -24.
-6x^{2}-30x-24=x^{2}-3x+2
Use the distributive property to multiply x-2 by x-1 and combine like terms.
-6x^{2}-30x-24-x^{2}=-3x+2
Subtract x^{2} from both sides.
-7x^{2}-30x-24=-3x+2
Combine -6x^{2} and -x^{2} to get -7x^{2}.
-7x^{2}-30x-24+3x=2
Add 3x to both sides.
-7x^{2}-27x-24=2
Combine -30x and 3x to get -27x.
-7x^{2}-27x=2+24
Add 24 to both sides.
-7x^{2}-27x=26
Add 2 and 24 to get 26.
\frac{-7x^{2}-27x}{-7}=\frac{26}{-7}
Divide both sides by -7.
x^{2}+\left(-\frac{27}{-7}\right)x=\frac{26}{-7}
Dividing by -7 undoes the multiplication by -7.
x^{2}+\frac{27}{7}x=\frac{26}{-7}
Divide -27 by -7.
x^{2}+\frac{27}{7}x=-\frac{26}{7}
Divide 26 by -7.
x^{2}+\frac{27}{7}x+\left(\frac{27}{14}\right)^{2}=-\frac{26}{7}+\left(\frac{27}{14}\right)^{2}
Divide \frac{27}{7}, the coefficient of the x term, by 2 to get \frac{27}{14}. Then add the square of \frac{27}{14} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+\frac{27}{7}x+\frac{729}{196}=-\frac{26}{7}+\frac{729}{196}
Square \frac{27}{14} by squaring both the numerator and the denominator of the fraction.
x^{2}+\frac{27}{7}x+\frac{729}{196}=\frac{1}{196}
Add -\frac{26}{7} to \frac{729}{196} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x+\frac{27}{14}\right)^{2}=\frac{1}{196}
Factor x^{2}+\frac{27}{7}x+\frac{729}{196}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+\frac{27}{14}\right)^{2}}=\sqrt{\frac{1}{196}}
Take the square root of both sides of the equation.
x+\frac{27}{14}=\frac{1}{14} x+\frac{27}{14}=-\frac{1}{14}
Simplify.
x=-\frac{13}{7} x=-2
Subtract \frac{27}{14} from both sides of the equation.